Influence of Fluid Therapy on the Prognosis of Acute Pancreatitis: A Prospective Cohort Study - de-Madaria, Enrique; Soler-Sala, Gema; Sánchez-Payá, José; Lopez-Font, Inmaculada; Martínez, Juan; Gómez-Escolar, Laura; Sempere, Laura; Sánchez-Fortún, Cristina; Pérez-Mateo, Miguel (The American journal of gastroenterology, 2011)
Although aggressive fluid therapy during the first days of hospitalization is recommended by most guidelines and reviews on acute pancreatitis (AP), this recommendation is not supported by any direct evidence. We aimed to evaluate the association between the amount of fluid administered during the initial 24 h of hospitalization and the incidence of organ failure (OF), local complications, and mortality. This was a prospective cohort study. We included consecutive adult patients admitted with AP. Local complications and OF were defined according to the Atlanta Classification. Persistent OF was defined as OF of >48-h duration. Patients were divided into three groups according to the amount of fluid administered during the initial 24 h: group A: <3.1 l (less than the first quartile), group B: 3.1-4.1 l (between the first and third quartiles), and group C: >4.1 l (more than the third quartile). A total of 247 patients were analyzed. Administration of >4.1 l during the initial 24 h was significantly and independently associated with persistent OF, acute collections, respiratory insufficiency, and renal insufficiency. Administration of <3.1 l during the initial 24 h was not associated with OF, local complications, or mortality. Patients who received between 3.1 and 4.1 l during the initial 24 h had an excellent outcome. In our study, administration of a small amount of fluid during the initial 24 h was not associated with a poor outcome. The need for a great amount of fluid during the initial 24 h was associated with a poor outcome; therefore, this group of patients must be carefully monitored.